How is the Quality of Tax Service in Covid-19 Pandemic Era? - Alfa Rahmiati; Lifia Inayah (Universitas Prasetiya Mulya, 2022)
In order to increase Indonesia tax revenue, the government issued a new regulation which made the task of the Account Representative even more important and focused on monitoring taxpayer compliance. This study aims to analyzes how tax services are implemented according to the latest tax regulations, especially in the era of the Covid-19 pandemic and how the quality those tax services. This study is a qualitative research using a case study approach. Data were collected from interviews with several AR at the RST Tax office. The result shows, in the era of the pandemic, the services provided by AR can still be carried out every day. AR has a reliable attitude and respects punctuality in service. Every question relating to taxation rights and obligations is explained in a coherent and complete manner in accordance with the information required by the Taxpayer. Further research analysis is needed to ensure the quality of AR services according to the taxpayer's view. https://doi.org/10.21632/irjbs.15.1.27-37